The concept of heroism and its representation in the novel “The Old Man and The Sea” - Sobirova Nurkhon Barot kizi (Zien Journals, 2022)
With the only word “hero”, a plethora of personages who make people or even the whole world astonished strike our minds in the blink of an eye. But there are such unique figures of the literature to whom worldly attention does not make any sense or the absence of millions of “eyes” is unable to hinder their heroic deeds. This can vividly be shown with the example of the fisherman Santiago in “The Old Man and The Sea” by Ernest Hemingway. “A man can be destroyed but not defeated” a statement made by the real hero-writer of the twentieth century whose epoch-making symbolic quotation echoes the invincible spirit of a hero who reaches the zenith of his success ultimately. In my study, I make an effort to find and analyze clear illustrations for the notion of heroism and represent it with the characters of the novel.
Keywords: Heroism; parallel suffering; dignity